Rudey's Windy Christmas - Helen Baugh (London Harpercollins Publisher, 2014)
An hilarious story full of noises and naughtiness. A sure-fire Christmas cracker of a book! 'Oh, dearie me!' said Rudey. Now I've done a windy pop! This is a bit embarrassing. I'll do my best to stop.' Rudey has eaten too many sprouts and the explosive effect is smelt all around the world as he helps Santa deliver presents on Christmas Eve. The other reindeer have laughed so much, they're out of puff. How ever will they get the sleigh back home?
Keywords: Independent Reading -- Independent Reading